Gas well testing handbook - Chaudhry, Amanat U. (Elsevier/Gulf Professional Pub., 2003)
This title deals exclusively with theory and practice of gas well testing, pressure transient analysis techniques, and analytical methods required to interpret well behavior in a given reservoir and evaluate reservoir quality, simulation efforts, and forecast producing capacity. A highly practical edition, this book is written for graduate students, reservoir/simulation engineers, technologists, geologists, geophysicists, and technical managers. The author draws from his extensive experience in reservoir/simulation, well testing, PVT analysis basics, and production operations from around the world and provides the reader with a thorough understanding of gas well test analysis basics. The main emphasis is on practical field application, where over 100 field examples are resented to illustrate basic methods for analysis. Simple solutions to the diffusivity equation are discussed and their physical meanings examined. Each chapter focuses in how to use the information gained in well testing to make engineering and economic decisions, and an overview of the current research models and their equations are discussed in relation to gas wells, homogenous, heterogeneous, naturally and hydraulically fractured reservoirs. Handy, portable reference with thousands of equations and procedures. There is currently no other reference or handbook on the market that focuses only on gas well testing. Offers "one stop shopping" for the drilling and reservoir engineer on gas well testing issues.
Keywords: Gas wells -- Testing -- Handbooks, manuals, etc.; elektronické knihy; electronic books